2019
DOI: 10.1111/srt.12711
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of transepidermal water loss, stratum corneum hydration and skin surface pH in occupational settings: A review

Abstract: Background The skin provides a permeable barrier which may be impaired in occupational settings. Transepidermal water loss (TEWL), stratum corneum hydration (SCH) and skin surface pH (SSpH) have been used in occupational settings to predict early onset of occupational skin diseases, to measure the effectiveness of prevention strategies for occupational skin diseases, and to assess skin condition during exposure. The aim was to compare the findings, identify shortcomings in the methodology and data reporting an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 40 publications
(209 reference statements)
4
58
0
2
Order By: Relevance
“…Normal hydration levels maintain SC flexibility and its viscoelastic characteristics in addition to facilitating the enzymatic reactions involved in the maturation of corneocytes [86,87]. Destabilization or damage to the skin surface by exposure to physical or chemical agents can cause changes in TEWL and SCH [88][89][90]. In this study, the evaluation of these parameters confirmed that APR-ME does not alter sebaceous function nor compromise the integrity of the skin barrier.…”
Section: Discussionsupporting
confidence: 72%
“…Normal hydration levels maintain SC flexibility and its viscoelastic characteristics in addition to facilitating the enzymatic reactions involved in the maturation of corneocytes [86,87]. Destabilization or damage to the skin surface by exposure to physical or chemical agents can cause changes in TEWL and SCH [88][89][90]. In this study, the evaluation of these parameters confirmed that APR-ME does not alter sebaceous function nor compromise the integrity of the skin barrier.…”
Section: Discussionsupporting
confidence: 72%
“…As shown in Figure 9A, the BTFM had sustained release effects at pH 5.5 and 7.4. Since the pH value of the epidermis (pH 5.5) is weakly acidic, 62,63 it is necessary to determine the release mechanism of berberine from BTFM at pH 5.5. The release kinetics of BTFM were fitted by Zero-order, Firstorder, Higuchi and Korsmeyer-Peppas, respectively.…”
Section: Dovepressmentioning
confidence: 99%
“…Due to the relatively large probe surface and multi‐sensory character of the Epsilon, all these areas were integrated into the measurement, while GPSkin values were determined based on only one sensor with a smaller probe. Moreover, if the SC is mostly removed, capacitance measurements primarily reflect the hydration state of the ‘wet’ stratum granulosum rather than the SC 23,29 ; especially the Epsilon device seems less reliable in this situation.…”
Section: Discussionmentioning
confidence: 99%
“…The measurements took place at the right volar forearm, because this location is easy to access, mainly refrained from UV‐light damage, hair, and sebaceous glands, and often used as a standard anatomical site for skin barrier studies 3,22‐24 . All procedures were performed by one investigator (JGML).…”
Section: Methodsmentioning
confidence: 99%